2018
DOI: 10.2147/ijn.s164518
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the oral delivery of Docetaxel: challenges, current state-of-the-art and future trends

Abstract: The oral delivery of cancer chemotherapeutic drugs is challenging due to low bioavailability, gastrointestinal side effects, first-pass metabolism and P-glycoprotein efflux pumps. Thus, chemotherapeutic drugs, including Docetaxel, are administered via an intravenous route, which poses many disadvantages of its own. Recent advances in pharmaceutical research have focused on designing new and efficient drug delivery systems for site-specific targeting, thus leading to improved bioavailability and pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 126 publications
(126 reference statements)
0
39
0
Order By: Relevance
“…Thus, much effort has been made for increasing the delivery and penetration of liposomal‐carried drugs into tumors, including NB . Although the so‐called “enhanced permeability and retention effect” (owing to leaky vessels typically present in tumors) has served as a rationale for using nanoformulated drugs to treat solid tumors, it is generally believed that this effect is not sufficient to guarantee uniform drug delivery to all tumor regions, because of the many physiological barriers, mentioned above, present in tumor tissues .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, much effort has been made for increasing the delivery and penetration of liposomal‐carried drugs into tumors, including NB . Although the so‐called “enhanced permeability and retention effect” (owing to leaky vessels typically present in tumors) has served as a rationale for using nanoformulated drugs to treat solid tumors, it is generally believed that this effect is not sufficient to guarantee uniform drug delivery to all tumor regions, because of the many physiological barriers, mentioned above, present in tumor tissues .…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of oral formulation has been difficult, because of the low oral bioavailability (<5%) of DTX [ 6 ]. The BCS class IV drug, DTX, is partially insoluble in water, and has low permeability across the gastrointestinal (GI) epithelium, due to P-glycoprotein (P-gp) mediated efflux, which limits the GI absorption and oral bioavailability of DTX [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Docetaxel has presented a broad spectrum of activity against various kinds of tumors. Because of its poor aqueous solubility (1–5 μg·mL −1 in plain water), the commercial docetaxel (Taxoter ® ) is currently formulated in a combination of tween 80 and ethanol to improve it solubility [ 15 , 16 , 17 ]. Studies have shown that preparations are known to cause severe peripheral neuropathy and allergic reactions.…”
Section: Introductionmentioning
confidence: 99%